Cp*Ir(iii)- and Cp*Rh(iii)-catalyzed C(sp2)–H amination of arenes using thioethers as directing groups. Issue 3 (16th December 2020) - Xie, Hui; Zhong, Mei; Wang, Xiao-Tong; Wu, Jia-Qiang; Cai, Yan-Qu; Liu, Jidan; Shu, Bing; Che, Tong; Zhang, Shang-Shi
Abstract : A mild and selective Cp*Ir(iii )- and Cp*Rh(iii )-catalyzed direct C(sp 2 )–H amination of arenes and three types of nitrene precursor reagents is reported, with the assistance of a thioether directing group. Abstract : A mild and selective Cp*Ir(iii )- and Cp*Rh(iii )-catalyzed direct C(sp 2 )–H amination of arenes and three types of nitrene precursor reagents is reported, with the assistance of a thioether directing group. This redox-neutral protocol proceeds under mild reaction conditions, has a broad substrate scope and high functional-group compatibility and generates the desired aminated products in moderate to excellent yields. The reaction represents the first example of a thioether-directed Cp*Ir(iii )- and Cp*Rh(iii )-catalyzed C(sp 2 )–H direct amination reaction. Moreover, azide compounds were employed as a diverse and robust aminating reagent for the first time in a thioether-directed C–H functionalization reaction.